EFISIENSI BAHAN BAKAR LIQUIFIED PETROLEUM GAS (LPG) SEBAGAI BAHAN BAKAR ALTERNATIF PADA MESIN BENSIN KAPAL PERIKANAN - Praditya, Argadian Yoga; Hutauruk, Ronald M; ', Nofrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in April to June 2016 at BBPI Semarang. The object of research is to determine the ratio between Liquified Petroleum Gas (LPG) and gasoline by its consumption and economy analysis.The experiment was conducted in laboratory (no burden), in the field of operation of fishing vessel and fishing trip. The data is analyzed using descriptive and economic analysis. The result of show that LPG as an alternative fuel is more efficient than gasoline for it can reduce 37 % of the use of fuel consumtion It reach around 0.88 kg / trip meanwhile gasoline is higher 0,62 kg/trip than LPG. From financial review, LPG also is the best in fishing effort small scale fishing operation where BCR 2.12, FRR 65.76% while the bank interest rate of bank is 5%, This means that the investment is acceptable to the gasoline. The fishing effort using LPG fuel is acceptable, where the value of FRR> bank rate. The maximum value PPC with an annual average was 1.52. This means that the payback period can be reached 1 year and 6 months 7 days Keywords: Fuel Efficiency, Fishing vessel, Gasoline engine, gasoline, LPG